Analysis of the Effect of Changes in Ignition Timing to Improve Engine Performance on a 155cc Automatic Motorcycle - Muhammad Fikri Aprilyansyah; Aripin; Deri Teguh Santoso (Universitas Medan Area, 2026)
This study aims to analyze the effect of using a Juken ECU with various settings on power, torque, fuel consumption, and specific fuel consumption on a motorcycle. Testing was conducted by comparing four conditions: the Standard ECU, the Juken ECU with standard settings, the Juken ECU with +2 settings, and the Juken ECU with -2 settings at speeds ranging from 30,000 to 70,000 mph.The test results showed that the highest power was achieved with the Juken ECU with -2 settings, with a maximum value of 10.07 hp at 70,000 mph. Meanwhile, the Juken ECU with -2 settings also achieved the highest torque of 9.19 Nm at the same speed. However, in terms of fuel efficiency, the Standard ECU demonstrated the lowest specific fuel consumption, indicating that this system is more efficient than the Juken ECU.Overall, it can be concluded that using the Juken ECU with -2 settings can improve engine performance in terms of power and torque, but at the same time, it also results in increased fuel consumption. The Standard ECU remains the most efficient choice for daily use that emphasizes fuel economy